Au nom du Père, contre lui et au‑delà de lui. Père inconnu de Pabé Mongo ou l’odyssée d’une bâtarde en quête d’affection paternelle - Eyenga Onana, Pierre Suzanne (Romanica Silesiana)
Using the explicit‑implicit socio‑critical approach systematized by Pierre Barberis, I will endeavour to trace the heuristic itinerary of a pugnacious illegitimate child in quest of her fugitive father. I will focus on textual clues and hermeneutical levers in order to reveal damages resulted in the absence of the father in the conjugal apparatus. In the first part, I will intend to prove that any paternal irresponsibility affects the vital equilibrium which is necessary to development within family and society. The second part, in turn, puts an emphasis on how psychological damages due to failed family life may result in reifying of minorities through the violation of women and children’s rights. Finally, I will endeavour to show that through the inter‑subjective gender approach one may see the project of a new world which fosters social justice for all sexes.